Concerted removal of the Erb1-Ytm1 complex in ribosome biogenesis relies on an elaborate interface - Thoms, Matthias; Ahmed, Yasar Luqman; Maddi, Karthik; Hurt, Ed; Sinning, Irmgard (Nucleic acids research, 2016)
Abstract. The complicated process of eukaryotic ribosome biogenesis involves about 200 assembly factors that transiently associate with the nascent pre-ribosom